YouTube jako nowe źródło wiedzy - Ciesiółka, Adrian (Neodidagmata, 2018)
The author of this article puts forward the thesis that YouTube is a new source of learning through, which educational functions are implemented, affecting the effectiveness of teaching and learning. The article presents the possibilities of realizing educational functions by YouTube. Research, conducted by the author, using a content analysis of media messages, constitutes an extension of the theoretical aspects considered in the initial part of the article, which concerns both, the context of the impact of the Internet on society, shaping the Internet space’s and website YouTube, and it’s educational potential. The aim of the research was to show to what extent YouTube implements educational functions. The analysis of the results of the conducted research indicates that the educational potential of YouTube is significant. The website fulfills many educational functions, including social ones. The article presents channels that implement educational functions and can be used as a source of knowledge.